Diagnosis-specific Cumulative Incidence of Return-to-work, Resignation, and Death Among Long-term Sick-listed Employees: Findings From the Japan Epidemiology Collaboration on Occupational Health Study - Chihiro Nishiura; Yosuke Inoue; Ikuko Kashino; Akiko Nanri; Motoki Endo; Masafumi Eguchi; Takeshi Kochi; Noritada Kato; Makiko Shimizu; Teppei Imai; Akiko Nishihara; Makoto Yamamoto; et al. (Journal of Epidemiology, 2022)
Background: While it is essential to understand how long is sufficient for return-to-work when designing paid sick-leave systems, little attempt has been done to collect cause-specific information on when and how many of sickness absentees returned to work, became unemployed, or passed away. Methods: We studied the first sick-leave episode of ≥30 consecutive days in those ≤55 years of age during 2012–2013 among employees of 11 Japanese private companies (n = 1,209), which were followed until 2017. Overall and disease-specific cumulative incidences of return-to-work, resignations, and deaths were estimated using competing risk analysis. Results: During the 3.5-year period (follow-up rate: 99.9%), 1,014 returned to work, 167 became unemployed, and 27 died. Overall, return-to-work occurred within 1 year in 74.9% of all absentees and in 89.3% of those who successfully returned to work. Resignation occurred within 1 year in 8.7% of all absentees and in 62.9% of all subjects who resigned. According to ICD-10 chapters, the cumulative incidence of return-to-work ranged from 82.1% for mental disorders (F00–F99) to 95.3% for circulatory diseases (I00–I99). The cumulative incidence of return-to-work due to mental disorders ranged from 66.7% in schizophrenia (F20) to 95.8% in bipolar affective disorders (F31). Death was rarely observed except for cases of neoplasms (C00–D48), of which the cumulative incidence of death reached 14.2% by 1.5 years. Conclusion: Return-to-work and resignations occurred commonly within 1 year of sick leave among long-term sickness absentees in the Japanese private companies. Our findings may assist occupational physicians and employers in developing effective social protection schemes.